2019
DOI: 10.1016/j.pedn.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Peer-led Asthma Self-management Group Intervention for Urban Adolescents

Abstract: Purpose: This paper describes the acceptability and generalizability of an evidenced-based peerled asthma self-management program. Design and Methods: Adolescents with persistent asthma (n=259, ages 12-17 years) from three urban cities participated in a one day camp led by either trained peer leaders (n= 35, ages 16-20 years; intervention group) or healthcare professionals (control group). Participants completed a camp evaluation form, and the peer leader quality survey. Results: Overall program evaluation sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Thus, careful evaluation of participants' acceptance of and satisfaction with treatment conditions could be part of fidelity assessment. In an earlier paper (Grape et al, ), we demonstrated high participant acceptance of and satisfaction with the program by participants in both groups, providing evidence of fidelity concerning treatment receipt.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, careful evaluation of participants' acceptance of and satisfaction with treatment conditions could be part of fidelity assessment. In an earlier paper (Grape et al, ), we demonstrated high participant acceptance of and satisfaction with the program by participants in both groups, providing evidence of fidelity concerning treatment receipt.…”
Section: Discussionsupporting
confidence: 66%
“…Each of the three participating cities used different venues for the 1 day camps. We describe details about the differences in the venues and camp structure across the three sites elsewhere (Grape, Rhee, & Sanchez, ). The education curriculum consisted of four sessions (asthma basics, symptom monitoring and prevention, asthma management, and management of psychosocial issues and communication).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study showed that a video-assisted interactive training was more successful in adolescents in terms of properly using of MDI (110) (16). In addition, group therapy and training with peers have increased the likelihood of properly use of inhaler device as shown in previous studies (17,18). Therefore, we believe that when teaching adolescents inhaler device use, the primary physician should prefer and use the above-mentioned methods.…”
Section: Discussionmentioning
confidence: 77%
“…Consequently, finding innovative ways to implement the intervention whilst still maintaining human contact, rather than taking a purely digital approach, is paramount. Recent work exploring the use of skype conferencing to deliver mindfulness interventions [27,30] or the use of lay facilitators to deliver interventions across conditions may be important avenues for further research [31][32][33].…”
Section: Discussionmentioning
confidence: 99%